2019
DOI: 10.1210/js.2019-mon-lb031
|View full text |Cite
|
Sign up to set email alerts
|

MON-LB031 Higher Insulin Degrading Enzyme Levels in Subjects with Metabolic Syndrome

Abstract: Background: With the growing prevalence of obesity, there is also a rise in the incidence of metabolic syndrome (MS). It is characterizes by hyperinsulinemia, increased fasting glucose, hypertriglyceridemia, low HDL, increased waist circumference and hypertension.Insulin-degrading enzyme (IDE) is the major enzyme responsible for insulin degradation among other proteins linked to glucose metabolism such as glucagon. Using genome wide associated studies, IDE was identified as a diabetes susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, Fosam and colleagues showed that in African Americans, who are at a higher risk for developing T2DM compared with non-Hispanic whites, lower IDE activity in the liver was associated with reduced insulin clearance and higher plasma insulin levels [ 111 ]. Sofer and colleagues found higher serum IDE levels in subjects with metabolic syndrome compared to control subjects [ 131 ]. Additionally, this group showed a direct correlation between circulating IDE levels and triglycerides, insulin, and C-peptide; whereas HDL-cholesterol was inversely associated [ 131 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Fosam and colleagues showed that in African Americans, who are at a higher risk for developing T2DM compared with non-Hispanic whites, lower IDE activity in the liver was associated with reduced insulin clearance and higher plasma insulin levels [ 111 ]. Sofer and colleagues found higher serum IDE levels in subjects with metabolic syndrome compared to control subjects [ 131 ]. Additionally, this group showed a direct correlation between circulating IDE levels and triglycerides, insulin, and C-peptide; whereas HDL-cholesterol was inversely associated [ 131 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sofer and colleagues found higher serum IDE levels in subjects with metabolic syndrome compared to control subjects [ 131 ]. Additionally, this group showed a direct correlation between circulating IDE levels and triglycerides, insulin, and C-peptide; whereas HDL-cholesterol was inversely associated [ 131 ]. Pivovarova and colleagues, using gene expression profiling by microarrays, showed decreased hepatic Ide expression in subjects with T2DM [ 132 ].…”
Section: Introductionmentioning
confidence: 99%